Psychoanalysis and American literature: Exploring the Relationship between Psychoanalysis and American Society (Journal of Advances and Scholarly Researches in Allied Education, 2013)
This focus on unconscious had an optimistic slant in America. Americans were not mistaken in seeing Freud as an optimist because Freud had hinted at the positive effect of psychological study. There were various questions related to psychoanalysis in America – why did America welcome psychoanalysis more warmly than any other country? What was the reason which created an affinity between psychoanalysis and American condition? To find out the answers of the above mentioned questions, one has to survey the whole field of psychoanalysis which Freud used for the practical Americans.